CREATIVE ECONOMIC ASSISTANCE THROUGH TRAINING FOR BOUQUET MAKING AND HALAL CERTIFICATION SOCIALIZATION - Hibati Wafiroh; Wisnu Azhari (Sekolah Tinggi Agama Islam Syubbanul Wathon Magelang, 2022)
Currently, micro businesses have an important role in society. The backbone of Indonesia's economy is through micro business because micro businesses are one of the government's programs for alleviating poverty. One of the efforts to promote micro business was carried out in Gondangan Hamlet, Sawangan Village, by training on making bouquets and socializing the creative economy. This activity is carried out to ignite the community's creativity and change the mindset to be more advanced. By using the ABCD (Asset Based Community Development) research method and the implementation method using the FGD method, interviews, presentations, and evaluations, the mindset of the Gondangan Hamlet community is increasingly advanced and systematic. It is proven by the number of people who are moved to start new creative businesses, and the community is aware of the importance of a certified economic system. People pay more attention to the economy and make something that looks worthless can be turned into something of high value. This needs to be maintained and even better because the progress of micro business in the community can advance the village economy and even the state.